IKON SEBAGAI IDENTITAS VISUAL DESA TENGANAN PEGRINGSINGAN - Widyaswari, I Gst Agung Ayu Widiari (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Visual identity is needed for companies and individuals, not least for the attractions to be more easily recognized and remembered by the public. One way to create a visual identity is through icons. The specific objective to be achieved in this research is to know and understand the icon elements in Tenganan Pegringsingan Traditional Village, which is studied in accordance with the sciences of Visual Communication Design. The results of this research will be used as a guide in designing an icon. This research is a qualitative descriptive study. Technique of collecting data is done through observation method, interview, and documentation. The results achieved is how the conformity of the concept and the form of icons are viewed based on the elements or elements of icon formers and the meaning contained therein.